Incidence, aetiology and outcome of community-acquired acute kidney injury in medical admissions in Malawi. Issue 1 (December 2017) - Evans, Rhys; Hemmilä, Ulla; Craik, Alison; Mtekateka, Mwayi; Hamilton, Fergus; Kawale, Zuze; Kirwan, Christopher; Dobbie, Hamish; Dreyer, Gavin
Abstract Background Epidemiological data on Acute Kidney Injury (AKI) from low-income countries is sparse. The aim of this study was to establish the incidence, severity, aetiology, and outcomes of community-acquired AKI in Malawi. Methods We conducted a prospective observational study of general medical admissions to a tertiary hospital in Blantyre between 27th April and 17th July 2015. All patients were screened on admission with a serum creatinine; those with creatinine above laboratory reference range were managed by the nephrology team. Hospital outcome was recorded in all patients. Results Eight hundred ninety- two patients were included; 188 (21 · 1%) had kidney disease on admission, including 153 (17 · 2%) with AKI (median age 41 years; 58 · 8% HIV seropositive). 60 · 8% of AKI was stage 3. The primary causes of AKI were sepsis and hypovolaemia in 133 (86 · 9%) cases, most commonly gastroenteritis (n = 29; 19 · 0%) and tuberculosis (n = 18; 11 · 8%). AKI was multifactorial in 117 (76 · 5%) patients; nephrotoxins were implicated in 110 (71 · 9%). Inpatient mortality was 44 · 4% in patients with AKI and 13 · 9% if no kidney disease (p <0.0001). 63 · 2% of patients who recovered kidney function left hospital with persistent kidney injury. Conclusion AKI incidence is 17 · 2% in medical admissions in Malawi, the majority is severe, and AKI leads to significantly increased in-hospital mortality. The predominant causes are infection and toxin related, both potentially avoidable and treatable relatively simply. Effective interventions are urgently required to reduce preventable young deaths from AKI in this part of the world.